Design and implementation of a digital site-less clinical study of serial rapid antigen testing to identify asymptomatic SARS-CoV-2 infection - Apurv Soni; Carly Herbert; Caitlin Pretz; Pamela Stamegna; Andreas Filippaios; Qiming Shi; Thejas Suvarna; Emma Harman; Summer Schrader; Chris Nowak; Eric Schramm; Vik Kheterpal; et al. (Journal of Clinical and Translational Science, 2023)
Abstract